I am reading my text, and they make a jump that I don't understand, and they don't give any explanation for it.

Sorry, I couldn't figure out how to put this stuff in latex...

mu=mean....greek letter (in particular, not m*u)

It gives the sum from i=1 to n of (xi-x bar)^2 + 2*(x bar-mu)*sum from i=1 to n of (xi-x bar)+n(x bar-mu)^2

It then says that this is equal to

sum from i=1 to n of (xi-x bar)^2 + n(x bar-mu)^2

Essentially they seem to be saying that

2*(x bar -mu)*sum from i=1 to n of (xi-x bar)

is zero

Is it because x bar- mu is 0? I didn't think this was the case......why is this middle term zero?